Geometrically flat hyperlens designed by transformation optics. (6th March 2019) - So, Sunae; Rho, Junsuk
Abstract: Here, we present a geometrically flat hyperlens that can still magnify and transfer sub-wavelength objects to the far-field. The flat hyperlens is designed using the transformation optics approach, which transforms the virtual space of the cylindrical coordinate into the physical space of the trapezoidal coordinate. We also suggest the possible design of two alternating multilayers by using an effective medium approximation. The sub-wavelength magnification using the designed flat hyperlens is numerically demonstrated. Such a flat hyperlens has great potential for practical application by solving many problems of conventional curvilinear hyperlenses arisen from their geometries.